Study On Waste Water Treatment Installation And Its Electricity Distribution - Noor Salim (Jurnal Teknik Elektro dan Komputasi (ELKOM), 2021)
Hospital wastewater is a source of pollutants for the environment that can have a negative impact. Hospital waste can contain various kinds of microorganisms depending on the type of hospital and the level of treatment carried out after the waste is disposed of. Therefore, it is necessary to conduct a study on Wastewater Treatment Plants so that the discharged wastewater meets the requirements of wastewater discharged from the hospital. From the results of this study it can be concluded that the initial process to the final process and after that it is necessary to check the quality of wastewater to determine the efficiency of treatment at least 2 times a year. The results of the Domestic WWTP engineering design are a capacity of 150 m3 per day, BOD of wastewater average 300 mg / l, SS concentration of 300 mg / l, total processing efficiency of 90-95%, BOD of treated water is 20 mg / l and SS treated water by 20 mg / l. Meanwhile, the distribution of electric power is in the form of MCB 1 phase 6 Amp - 220 Volt with a power of 1122 watts which is used to supply 1 unit of 250 watts of recycler pumps and 4 units of air / blower pumps of 800 watts or a total requirement of 1050 watts. Whereas for the MCB 3 phase 32 Amp - 380 Volt with a power of 17,902,478 watts, it is used to supply 10 units of the pump for collecting tubs of 3500 watts and 1 unit of wastewater pumps of 350 watts or a total requirement of 3,850 watts. It is recommended that the fat filter tub be transported every day so that grease and other impurities do not accumulate., The sewage pipe that is found to have leaks should be repaired immediately and there is a need for fish in the control tub which functions as a control medium as an indicator that the waste treatment process is going well.